2020
DOI: 10.3390/ijms21114142
|View full text |Cite
|
Sign up to set email alerts
|

Profound Nanoscale Structural and Biomechanical Changes in DNA Helix upon Treatment with Anthracycline Drugs

Abstract: In our study, we describe the outcomes of the intercalation of different anthracycline antibiotics in double-stranded DNA at the nanoscale and single molecule level. Atomic force microscopy analysis revealed that intercalation results in significant elongation and thinning of dsDNA molecules. Additionally, using optical tweezers, we have shown that intercalation decreases the stiffness of DNA molecules, that results in greater susceptibility of dsDNA to break. Using DNA molecules with different GC/AT ratios, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Adding equations (2) and (3) and multiplying by equation (1) yields the following function: which was used to fit all the measured FECs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding equations (2) and (3) and multiplying by equation (1) yields the following function: which was used to fit all the measured FECs.…”
Section: Methodsmentioning
confidence: 99%
“…The advent and perfection of single-molecule methods in the recent decades have led to unprecedented new insights into the mechanisms and properties of biomolecular processes, and pointed out that mechanical forces and molecular nanomechanics play a much more important role in controlling cellular and sub-cellular phenomena than earlier thought. DNA has particularly been in the focus of single-molecule experiments, as the molecule lends itself naturally to exploring the role of its axial, bending, twisting and strand-separation nanomechanics in DNA-associated processes (1)(2)(3)(4)(5). The combination of novel methodologies, for example, optical tweezers, microfluidics and high-resolution fluorescence microscopies, has paved the way towards understanding how DNA nanomechanics are influenced by external factors such as intercalators (6), binding proteins (7) or solute concentration gradients (8).…”
Section: Introductionmentioning
confidence: 99%
“…The anthracycline drug idarubicin has been used for decades predominantly for the treatment of acute myeloid leukemia (AML) and acute nonlymphocytic leukaemia (ANLL), especially in paediatric populations. The main mechanisms underlying the antiproliferative effects of anthracyclines consist of intercalation and cross-linking of DNA and of inhibition of the topoisomerase II leading to disturbed DNA synthesis (Pommier et al 2010 ; Marinello et al 2018 ; Kaczorowska et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dissecting out the intrinsic mechanisms of action of anthracycline compounds is expected to advance the pharmaceutical development of more specific anticancer therapies while depressing their original undesirable side effects. Many studies have shown that DM acts as a topoisomerase II (Top2) inhibitor, where cell killing is caused through the generation of DNA double-strand breaks (DSBs) due to Top2 poisoning [ 6 , 7 , 9 , 10 , 13 , 14 , 15 , 16 , 17 ]. Wang et al argued that anthracyclines interact at the interface of Top2-DNA with their sugar moieties and the cyclohexane ring A [ 13 ].…”
Section: Introductionmentioning
confidence: 99%